2008
DOI: 10.1007/s12311-008-0043-y
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Purkinje Cells are Reduced in a Subpopulation of Autistic Brains: A Stereological Experiment Using Calbindin-D28k

Abstract: Although a decreased number of cerebellar Purkinje cells (PCs) in the autistic brain has been widely reported with a variety of qualitative and quantitative methods, the more accurate method of cell counting with modern stereology has not yet been employed. An additional possible problem with prior reports is the use of Nissl staining to identify the PCs, as this can miss cells due to staining irregularities. In the present study, PCs were immunostained for calbindin-D28k (CB), as this has been shown to be a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
162
1
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(176 citation statements)
references
References 42 publications
9
162
1
4
Order By: Relevance
“…PC loss has been observed in several autopsy studies of autistic patients (Palmen et al, 2004;Whitney et al, 2008;Skefos et al, 2014;Wegiel et al, 2014). Regarding animal models, Lurcher chimeric mice, which show cerebellar abnormalities including postnatal loss of PCs, display behavioral inflexibility and repetitive behavior (Martin et al, 2010).…”
Section: Pcs and Autismmentioning
confidence: 99%
See 1 more Smart Citation
“…PC loss has been observed in several autopsy studies of autistic patients (Palmen et al, 2004;Whitney et al, 2008;Skefos et al, 2014;Wegiel et al, 2014). Regarding animal models, Lurcher chimeric mice, which show cerebellar abnormalities including postnatal loss of PCs, display behavioral inflexibility and repetitive behavior (Martin et al, 2010).…”
Section: Pcs and Autismmentioning
confidence: 99%
“…The cerebellum is involved not only in the control of balance, motor coordination, and learning, but also in higher order emotional, social, and cognitive functions, mainly through its projections (via the thalamus) to various cortical regions including the prefrontal, parietal, and limbic cortex (Fatemi et al, 2012;Reeber et al, 2013;Strick et al, 2009). Notably, Purkinje cell (PC) loss is one of the most common anatomical abnormalities seen in autopsy studies of autistic patients (Palmen et al, 2004;Whitney et al, 2008;Skefos et al, 2014;Wegiel et al, 2014). Cerebellar injury has been associated with a high incidence of ASDs (Wang et al, 2014), and patients with diseases confined to the cerebellum often demonstrate abnormalities seen in ASDs (Schmahmann, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Morphological or density changes of PCs in the cerebellum are primarily determined by immunohistochemical (IHC) analysis using PC-specific biomarkers that discriminate PCs from other types of cells in the cerebellum (Haworth et al, 2006;Whitney et al, 2008a). Calbindin D28k (CaB), a member of calcium-binding protein superfamily, is a PCspecific protein in the cerebellum (Bastianelli, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of evidence showing associations between ASD and neurodegeneration, including loss of neuronal cells, activation of microglia and astrocytes, and elevation of proinflammatory cytokines and oxidative stress [176,177]. Several post-mortem brain tissue studies have reported a decreased number of cerebellar Purkinje cells (PC), which function in modulating various cognitive and motor behaviors [178][179][180]. Using stereology and calbindin-D28k (CB) immunostaining, Whitney et al [180] found that, in autistic groups, Purkinje neurons were generated, and migrated to their proper location in the Purkinje layer, but were subject to subsequent neurodegeneration.…”
Section: Genes Involved In Neurodegenerationmentioning
confidence: 99%
“…Several post-mortem brain tissue studies have reported a decreased number of cerebellar Purkinje cells (PC), which function in modulating various cognitive and motor behaviors [178][179][180]. Using stereology and calbindin-D28k (CB) immunostaining, Whitney et al [180] found that, in autistic groups, Purkinje neurons were generated, and migrated to their proper location in the Purkinje layer, but were subject to subsequent neurodegeneration. Moreover, gliosis (a sign of glial activation) was also reported to accompany neuronal degeneration in the cerebellum [178].…”
Section: Genes Involved In Neurodegenerationmentioning
confidence: 99%